Hall effect sensors using polarized electron cloud spin orientation control. Issue 3 (7th October 2020) - Arumona, Arumona Edward; Garhwal, Anita; Youplao, Phichai; Amiri, Iraj Sadegh; Ray, Kanad; Punthawanunt, Suphanchai; Yupapin, Preecha
Abstract: A silicon microring circuit embedded gold film with unique characteristics is proposed for Hall effect, current, and temperature sensing applications. The microring circuit is operated by the input polarized laser sources, in which the space–time distortion control can be employed. A gold film is embedded at the microring center. The whispering gallery mode (WGM) is generated and applied for plasmonic waves, from which the trapped electron cloud oscillation is formed. Through the input port, the input polarized light of 1.55 μm wavelength fed into the space–time control circuit. Spin‐up |↑〉(|0〉) and spin‐down |↓〉(|1〉) of polarized electrons result when the gold film is illuminated by the WGM. The electric current passing through the gold film generates a magnetic field ( B ), which is orthogonal to the electric field. Hall voltage is obtained at the output of the circuit, from which the microring space–time circuit can operate for Hall's effect, current, and temperature sensing device. The simulation results obtained have shown that when the input power of 100–500 mW is applied, the optimum Hall effect, current, and temperature sensitivities are 0.12 μVT −1, 0.9 μVA −1, and 6.0 × 10 −2 μVK −1, respectively. The Hall effects, current, and temperature sensors have an optimum response time of 1.9 fs. Abstract : Hall effect sensors using polarized electron cloud spin is novel. This is a compact device with realistic parameters that can be fabricated and implemented. The proposed circuit can be applied for voltage, current, and temperature sensors. By using the electron cloud spin, the related microscopic sensors can be applied. The wireless (remote) sensor is also possible.